2015
DOI: 10.1001/jamaoto.2014.2826
|View full text |Cite
|
Sign up to set email alerts
|

Adult-Onset Recurrent Respiratory Papillomatosis

Abstract: Recurrent respiratory papillomatosis may be related to a new or latent HPV infection, potentially obtained at birth, and the mechanism(s) underlying the progression from HPV infection to RRP remains unknown. Recommendations with regard to sexual practices in patients with AO-RRP cannot be made at this time. Unlike human immunodeficiency virus, patients with AO-RRP are not obligated to discuss infection status with partners. Despite the nebulous nature of the disease, clinicians should be a resource to discuss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 56 publications
1
19
1
Order By: Relevance
“… 3 , 15 , 16 ) The adult form begins after the age of 20, being more common in males in the third or fourth decades of life. 3 , 4 , 9 , 17 , 18 ) Orlamd et al, 19 studying 224 patients, found that 174 (77.7%) had the juvenile form of the disease, whereas 50 (22.3%) had the adult form. Among the children in that study, 81% were male.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 15 , 16 ) The adult form begins after the age of 20, being more common in males in the third or fourth decades of life. 3 , 4 , 9 , 17 , 18 ) Orlamd et al, 19 studying 224 patients, found that 174 (77.7%) had the juvenile form of the disease, whereas 50 (22.3%) had the adult form. Among the children in that study, 81% were male.…”
Section: Discussionmentioning
confidence: 99%
“…Second, high-risk HPV 18, and in rare cases other high-risk mucosal types and low-risk mucosal HPV 6 and 11 were detected in the HNSCC ( Gillison et al , 2000 ; Kreimer et al , 2005 ). However, the latter two types predominantly cause papillomas of the respiratory and the laryngeal tract, including recurrent respiratory papillomatosis, a rare disease in children and adults that due to extensive warty growths in the upper airway and dissemination to bronchi, may cause significant airway obstruction and may undergo malignant transformation ( Venkatesan et al , 2012 ; Taliercio et al , 2015 ).…”
mentioning
confidence: 99%
“…Some data question the dogma that active and passive smoking plays a role in recidivistic disease [1517]. Several authors have also questioned the role of laryngopharyngeal reflux (LPR), mainly because of the lack of well-designed studies and less than ideal diagnostic methods of LPR, which were mostly limited to questionnaires or indirect signs of reflux, in existing studies [16, 18, 19].…”
Section: Introductionmentioning
confidence: 99%